The Effect of Income on Capital Expenditure with Budget Surplus as a Moderating Variable - Sucito, Andi; Abdullah, Syukriy; Darwanis, Darwanis (Riviera Publishing, 2023)
The realization of capital expenditure of regencies/cities in North Sumatra Province during the 2019-2020 period decreased by more than 25%. Similarly, the realization of local indigenous income (PAD) in the province decreased in 2019-2020 by 4.75%. This decrease is thought to be caused by poor budget planning at the beginning of the budgeting year. This study aims to determine the effect of local income and general allocation funds on capital expenditure moderated by budget surplus in districts/cities in north Sumatra province in 2016-2020. This study uses descriptive quantitative method. The population of this study is all regencies/cities in North Sumatra Province which amounts to 33 regencies/cities. This study used multiple linear regression techniques to determine the influence between research variables. The results showed that local original income had a positive effect on capital expenditure, the general allocation fund had a positive effect on capital expenditure, the budget surplus moderated the effect of local original income on capital expenditure, and the surplus budget moderated the effect of the general allocation fund on district/city capital expenditure in North Sumatra Province 2016-2020. The increase in PAD and DAU will have a positive impact on Capital Expenditure of Regencies/Cities in North Sumatra Province. The increase in PAD and DAU will provide sufficient budget for local governments to finance the necessary development projects. This can have a positive impact, including the availability of sufficient budgets, improving community welfare, increasing economic growth, and increasing regional competitiveness.